2023
DOI: 10.3389/fams.2023.1153666
|View full text |Cite
|
Sign up to set email alerts
|

Modeling visceral leishmaniasis and tuberculosis co-infection dynamics

Abstract: The co-infection of visceral leishmaniasis (VL) and tuberculosis (TB) patients pose a major public health challenge. In this study, we develop a mathematical model to study the transmission dynamics of VL and TB co-infection by first analyzing the VL and TB sub-models separately. The dynamics of these sub-models and the full co-infection model are determined based on the reproduction number. When the associated reproduction number (R1) for the TB-only model and (R2) for the VL-only are less than unity, the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Furthermore, tuberculosis may cause progression of latent leishmaniasis to the clinical stage, while visceral leishmaniasis can also reactivate latent tuberculosis. Thus, pulmonary tuberculosis and leishmaniasis (as well as other parasitic diseases) have been shown to be risk factors for each other [ 10 ] and due to their geographical overlap, co-infections are very common [ 11 , 12 , 13 , 14 ]. The low level of development of the countries with the highest prevalence of both infections makes the simultaneous treatment of these diseases difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, tuberculosis may cause progression of latent leishmaniasis to the clinical stage, while visceral leishmaniasis can also reactivate latent tuberculosis. Thus, pulmonary tuberculosis and leishmaniasis (as well as other parasitic diseases) have been shown to be risk factors for each other [ 10 ] and due to their geographical overlap, co-infections are very common [ 11 , 12 , 13 , 14 ]. The low level of development of the countries with the highest prevalence of both infections makes the simultaneous treatment of these diseases difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive studies over the years revealed that mathematical modeling and simulation can play a significant role in understanding the reasons for diverse infectious diseases, thereby predicting the possible cure. It is needless to say that mathematical modeling of VL has a rich history wherein numerous reports exist on the classical, fractional, statistical, machine learning models, and so forth [1][2][3][4][5][6][7][8][9]. In addition, it was acknowledged that the fractional calculus can offer deep insights into the dynamics of VL, leading to more accurate model and effective treatment strategies.…”
Section: Introductionmentioning
confidence: 99%